Analysis of floodwater: A Case Study of the Tukad Buluk Poh River - Hidayat, Acep; Praptoyo, Riska Dwi; Isradi, Muhammad; Suprapti, Suprapti (Universitas Mercu Buana, 2024)
One of the main causes of flooding is the disruption of river flow due to silting or narrowing of the river basin. The high volume of water in the rivershed will overflow and cause flooding in the surrounding area of the river. The object of this research is the Tukad Biluk Poh River, a river in the Jembrana district, Bali, which has 28 km long and empties into the Indian Ocean. The study aims to measure a flood water level limit at the river bridge that crosses the National Highway Gilimanuk-Denpasar so flooding on that section can be avoided. This quantitative descriptive research analysis uses the Nakayasu HSS (Synthetic Unit Hydrograph of Nakayasu) method for a while in 2, 5, 10, 25, 50, 100, 200, and 1000 years. Next, a hydraulics analysis to determine the flood water level limit uses the HEC-RAS model and results in MAB heights for a similar period. The research results revealed the height at the pavement section and the bottom of the girder section. At the end of this paper, the height of bridge that needs to be elevated at the bottom of the bridge's upper structure and a guard height for a certain repeat time are discussed. Therefore, it is believed that the research outcome will make an important contribution to the local government in issuing the Tukad Biluk Poh rivershed policy.